Common fixed point theorems on non-complete partial metric spaces - Sedghi, Shaban; Shobkolaei, Nabi; Altun, Ishak (Nonlinear Analysis: Modelling and Control, 2013)
In the peresent paper, we give a common fixed point theorem for four weakly compatible mappings on non-complete partial metric spaces. Some supporting examples are provided.